Albuminuria as a marker of systemic congestion in patients with heart failure. (23rd September 2022) - Boorsma, Eva M; ter Maaten, Jozine M; Damman, Kevin; van Essen, Bart J; Zannad, Faiez; van Veldhuisen, Dirk J; Samani, Nilesh J; Dickstein, Kenneth; Metra, Marco; Filippatos, Gerasimos; Lang, Chim C; Ng, Leong; et al.
Abstract: Aims: Albuminuria is common in patients with heart failure and associated with worse outcomes. The underlying pathophysiological mechanism of albuminuria in heart failure is still incompletely understood. The association of clinical characteristics and biomarker profile with albuminuria in patients with heart failure with both reduced and preserved ejection fractions were evaluated. Methods and results: Two thousand three hundred and fifteen patients included in the index cohort of BIOSTAT-CHF were evaluated and findings were validated in the independent BIOSTAT-CHF validation cohort (1431 patients). Micro-albuminuria and macro-albuminuria were defined as urinary albumin–creatinine ratio (UACR) >30 mg/gCr and >300 mg/gCr in spot urines, respectively. The prevalence of micro- and macro-albuminuria was 35.4% and 10.0%, respectively. Patients with albuminuria had more severe heart failure, as indicated by inclusion during admission, higher New York Heart Association functional class, more clinical signs and symptoms of congestion, and higher concentrations of biomarkers related to congestion, such as biologically active adrenomedullin, cancer antigen 125, and N-terminal pro-B-type natriuretic peptide (NT-proBNP) (all P < 0.001). The presence of albuminuria was associated with increased risk of mortality and heart failure (re)hospitalization in both cohorts. The strongest independent association with log UACR was found for log NT-proBNP (standardized regression coefficient 0.438, 95% confidence interval 0.35–0.53, P < 0.001). Hierarchical clustering analysis demonstrated that UACR clusters with markers of congestion and less with indices of renal function. The validation cohort yielded similar findings. Conclusion: In patients with new-onset or worsening heart failure, albuminuria is consistently associated with clinical, echocardiographic, and circulating biomarkers of congestion. Structured Graphical Abstract: Structured Graphical Abstract Graphical summary of the main findings of the current study. Prevalence and hazard ratio are based on the index cohort. HF, heart failure; UACR, urinary albumin–creatinine ratio; HR, hazard ratio. Created with BioRender.com.